2021
DOI: 10.1155/2021/8099451
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental Study on Alleviating Sports Injury through Data Screening of Functional Motor Biological Images

Abstract: In order to better reduce sports injury, a method based on functional motion biological image data is proposed. Through performing functional motion screening test on wushu athletes, including 7 items of test, each athlete is given a score according to the test standard. This paper summarizes the mistakes and deficiencies of common movement patterns of athletes and makes different intervention plans to improve the effect of sports injury screening. The results show that, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…erefore, in creating a physical exercise program, it is essential to incrementally increase mechanical load through the practice season as athletes become conditioned. Rao [9] proposed a dynamic, recursive model for risk assessment and causes of sports injuries and proposed that the injury has a nonlinear behavior. is model is helpful in the understanding of sports injury etiology because it proposes that there may be recurrent changes in susceptibility to injury along with the participation in sports, and the primary risk factors' exposure can produce adaptations and continuously change the risk.…”
Section: Introductionmentioning
confidence: 99%
“…erefore, in creating a physical exercise program, it is essential to incrementally increase mechanical load through the practice season as athletes become conditioned. Rao [9] proposed a dynamic, recursive model for risk assessment and causes of sports injuries and proposed that the injury has a nonlinear behavior. is model is helpful in the understanding of sports injury etiology because it proposes that there may be recurrent changes in susceptibility to injury along with the participation in sports, and the primary risk factors' exposure can produce adaptations and continuously change the risk.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%